Conservation agriculture and sustainable development in Africa: insights from Tanzania. (29th March 2017) - Scheba, Andreas
Abstract : In recent years, conservation agriculture (CA) has been increasingly promoted as the best solution to sustainable agricultural development in Africa. Proponents argue that it offers increased yields, reduced labour requirements, improved soil fertility and climate mitigation benefits. At the same time, a growing number of scholars have questioned its promises, impacts and applicability to small, resource‐poor African farmers. To add to the debate, this paper draws on fieldwork from two case study villages in the Lindi region of Tanzania. It scrutinizes CA farmer field schools' performances, the impact on villagers' perceptions of core principles and socio‐economic/institutional constraints related to its adoption. It demonstrates how farmer field schools failed to meet initial expectations because of challenges associated with economic benefits, labour demand, availability and accessibility of inputs, infrastructure, governance, and stakeholder relations. It argues that the applicability to and adoption of CA depends on the transformation of individual perceptions as well as structural constraints, including credit facilities, markets for inputs, infrastructure and availability of labour, which has long been a limitation of donor‐initiated programmes. Under constraining socio‐economic and institutional conditions, questions continue to loom large over the long‐term applicability of CA to African smallholder farmers.